Socializing IR: Turkish IR Scholars and their Twitter Interactions - Mehmetcik, Hakan; Morgan, Eric Lease; Kölük, Melih; Yüksel, Galip (İhsan Doğramacı Barış Vakfı, 2024)
[Abstract Not Available]
Keywords: Uluslararası İlişkiler